OP0182 Prevention of Rheumatoid Arthritis by B Cell Directed Therapy in The Earliest Phase of The Disease: The Prairi Study. (15th July 2016) - Gerlag, D.; Safy, M.; Maijer, K.; de Hair, M.; Tas, S.; Starmans-Kool, M.; van Tubergen, A.; Janssen, M.; Tak, P.-P.
Abstract : Background: Systemic autoimmunity may precede the development of clinical signs and symptoms of seropositive rheumatoid arthritis (RA), which offers a window of opportunity to delay or prevent clinically manifest arthritis by targeted intervention. This could represent a paradigm shift from treatment to prevention 1 . Objectives: To explore if a single infusion of rituximab (anti-CD20 antibody) can prevent or delay the onset of clinically manifest arthritis in individuals at risk of developing autoantibody positive RA. Methods: Eighty-two subjects with arthralgia who had never had clinically manifest arthritis and never used disease-modifying antirheumatic drugs were included in a multicentre, randomised, double-blind, placebo-controlled clinical trial. They were positive for both anti-citrullinated protein antibodies (ACPA) and rheumatoid factor and they had CRP levels ≥3 mg/l and/or subclinical synovitis on ultrasound or MRI of the hands. Subjects were randomized to receive a single iv infusion of either 1000 mg rituximab or placebo after 100 mg methylprednisolone premedication in each group. Subjects were prospectively followed to assess development of clinically manifest arthritis. We performed Kaplan-Meier survival analysis, Cox regression analysis and determined Treatment*Time Cox proportional hazards. Results: Eighty-one individuals (52 females; mean age 53 (IQR 13.5) years) received treatment, which was generally well tolerated. One patient withdrew before treatment. The median follow up was 27.0 months (IQR 25.0), during which 30 subjects developed arthritis: 16/40 (40%) in the placebo group and 14/41 (34%) in the rituximab group, after a median period of 11.5 (interquartile range [IQR] 12.5) months in the placebo group versus 16.5 (IQR 19.0) months in the rituximab group. Whereas the risk for development of arthritis in the placebo group was 40%, we found a reduction of 53% of this risk in the rituximab group at 18 months follow up (HR (95%CI)=0.475 (0.190–1.191)). At the 25% quartile (75% free of arthritis) of the cumulative arthritis-free survival, there was a delay in the development of arthritis of 12.0 months (12 months in the placebo group versus 24 months in the rituximab group. As expected, this effect attenuated over time. Treatment*Time Cox proportional hazard analysis showed that the beneficial effect of rituximab was statistically significant (P<0.0001) Conclusions: A single infusion of 1000 mg rituximab significantly delays the development of arthritis in subjects at risk of developing RA. This is the first study evaluating the effects of a biopharmaceutical in this population, and the results strongly support the rationale for future clinical trials aimed at prevention of RA by a targeted intervention. References: Gerlag DM, Norris JM, Tak PP. RA: from risk factors and pathogenesis to prevention: Towards prevention of autoantibody-positive rheumatoid arthritis: from lifestyle modification to preventive treatment. Rheumatology (Oxford). 2015 Sep 15. Review Acknowledgement: N de Vries, DJ van Schaardenburg, E Brouwer, T Huizinga Disclosure of Interest: D. Gerlag Shareholder of: GlaxoSmithKline, Grant/research support from: Dutch Arthritis Foundation, Netherlands Organisation for Health Research and Development, Employee of: GlaxoSmithKline, M. Safy: None declared, K. Maijer: None declared, M. de Hair: None declared, S. Tas: None declared, M. Starmans-Kool: None declared, A. van Tubergen: None declared, M. Janssen: None declared, P.-P. Tak Shareholder of: GlaxoSmithKline, Grant/research support from: Dutch Arthritis Foundation, Netherlands Organisation for Health Research and Development, Employee of: GlaxoSmithKline